Treatment decisions after interdisciplinary evaluation for nonarthritic hip pain: A randomized controlled trial. Issue 3 (16th August 2021) - Brown‐Taylor, Lindsey; Harris‐Hayes, Marcie; Foraker, Randi; Vasileff, William Kelton; Glaws, Kathryn; Di Stasi, Stephanie
Abstract: Background: Physical therapy and hip arthroscopy are two viable treatment options for patients with nonarthritic hip pain (NAHP); however, patients may experience considerable decisional conflict when making a treatment decision. Interdisciplinary evaluation with a physical therapist and surgeon may better inform the decision‐making process and reduce decisional conflict. Objective: To identify the extent to which an interdisciplinary evaluation between a surgeon, physical therapist, and patient influences treatment plans and decisional conflict of persons with NAHP. Design: Randomized controlled trial. Setting: Hip preservation clinic. Participants: Adults with primary NAHP. Interventions: Participants were randomized to receive a standard (surgeon) or interdisciplinary (surgeon+physical therapist) evaluation. Surgeon evaluations included patient interview, strength and range‐of‐motion examination, palpation, gross motor observation, and special testing. Interdisciplinary evaluations started with the surgeon evaluation, then a physical therapist evaluated movement impairments during sitting, sit‐to‐stand, standing, single‐leg stance, single‐leg squat, and walking. All evaluations concluded with treatment planning with the respective provider(s). Outcome Measures: Treatment plan and decisional conflict were collected pre‐ and postevaluation. Inclusion of physical therapy in participants' postevaluation treatment plans and postevaluation decisional conflict were compared between groups using chi‐square tests and Mann‐Whitney U tests, respectively. Results: Seventy‐eight participants (39 in each group) met all eligibility criteria and were included in all analyses. Sixty‐six percent of participants who received an interdisciplinary evaluation included physical therapy in their postevaluation treatment plan, compared to 48% of participants who received a standard evaluation ( p  = .10). Participants who received an interdisciplinary evaluation reported 6.3 points lower decisional conflict regarding their postevaluation plan (100‐point scale; p  = .04). The interdisciplinary and standard groups reduced decisional conflict on average 24.8 ± 18.9 and 23.6 ± 14.6 points, respectively. Conclusions: Adding a physical therapist to a surgical clinic increased interest in physical therapy treatment, but this increase was not statistically significant. The interdisciplinary group displayed lower postevaluation decisional conflict; however, both groups displayed similar reductions in decisional conflict from pre‐ to postevaluation. This study also demonstrated the feasibility of an interdisciplinary evaluation in a hip preservation clinic.